Pemikiran Pendidikan Karakter Ibn Miskawaih (Telaah Filosofis) - Ihwani, Ahmad; Noupal, Muhammad; Sandi, Ari (Sekolah Tinggi Agam Islam Sumatera Medan, 2020)
This study aims to analyze the concept of character education according to Ibn Miskawaih in a philosophical perspective with a focus on studies from the side of ontology, epistemology, and axiology. The research method used is the library research method. Sources of literature in this study consist of primary sources and secondary sources. The primary source of literature is the book of tahzib al-Akhlak, and the secondary source is references related to character education such as other books from Ibn Miskawaih's essays, journals, or proceedings. Data analysis begins with unit processing, categorization, and ends with data interpretation. The results showed that ontologically, character education is an effort to curb the three forces that exist in the human soul, so that all body activities become good and spontaneous without the need for prior consideration. Epistemologically, the character education method includes willpower, self-introspection, thariqun thabi'iyyah and opposition methods. Axiologically, character education boils down to the middle path (al-wasath), with main virtues such as al-hikmah (wisdom), al-'iffah (maintaining self-purity), as-Saja'ah (courage) and al-'adalah ( justice).